Improving Sexual Function in Perimenopause Women with Loving Yoga Exercise - Rizka Ayu Setyani; Fika Lilik Indrawati (Jurnal Kebidanan dan Kesehatan Tradisional, 2021)
Background: Reduced vaginal mucus to dyspareunia (pain during intercourse) is often experienced by perimenopausal women. This decreases sexual drive and awakening in women who influence sexual quality with their partner. One of the body and mind intervention exercises in premenopausal women is loving yoga. This study aims to find out the effectiveness of loving yoga against the sexual function of perimenopausal women. Methods: This type of research is a quantitative experiment with a one-group pretest-posttest design approach. Research by giving loving yoga intervention for four weeks (with intensity twice a week). Loving yoga movement focuses on kegel gymnastics and pelvic muscle movements, such as plank movement, upward dog, happy baby, downward-facing dog, cat-cow, pigeon, cobbler, leg-up-the-wall, reclining-big-toe, and bridge. Researchers measured the sexual function in 30 women by purposive sampling with inclusion criteria were aged 40-50 and still sexually active before and after loving yoga using the Female Sexual Function Index (FSFI) questionnaire. Analyze data using paired sample T-test. Results: This study result is seen from the mean value of 14.33, which means the FSFI score ≤ 26.5. While after complementary therapy loving yoga, the mean value of respondents is 30.13 or an FSFI score ≥ of 26.5, which means no sexual dysfunction. Based on the calculated Paired T-Test variables, the sexual function is obtained at the value of –28,748 with a significance value of < 0,000 (p < 0,05). Conclusion: Loving yoga has an influence 28,748 times on changes in the sexual function in perimenopausal women.